The views and experiences of families and support workers regarding the expression of sexuality by adults with intellectual disabilities: A narrative review of the international research evidence - Mc Cann, Edward; Brown, Michael (My University, 2019)
Background There is a growing and evolving research evidence base regarding sexuality issues and adults with intellectual disabilities. However, the experiences of families and direct care support workers and their support and development needs in the topic area remains elusive. Aims The aim of this review was to explore the views and experiences of families and direct care support workers in relation to the expression of sexuality by adults with intellectual disabilities and to identify their distinct support and development needs. Methods and procedures A comprehensive search of relevant databases from May 1998 to June 2018 was undertaken. Included studies had to address specific criteria including: peer reviewed papers, the use of appropriate research methods, and focused exclusively on the individual views and opinions of families and direct care support workers. The search of relevant databases yielded 313 hits. Following the application of explicit inclusion and exclusion criteria, 11 papers were deemed suitable for the review. Outcomes and results The data were analyzed and key findings highlighted issues for families and direct care support workers including: attitudes and beliefs; fear of abuse, exploitation and harm; new technologies; policies and guidelines; and education and training programmes. Conclusions and Implications Families and direct care support workers have specific support and education needs. Future healthcare initiatives need to be developed that are fully responsive to the identified concerns and requirements of families and direct care support workers.
PUBLISHED
Keywords: Family; Support workers; Intellectual disabilities; adults; Systematic review; Inclusive Society; FAMILIES; INTELLECTUAL DISABILITIES; Sexuality; support workers